1975
DOI: 10.1002/eji.1830051208
|View full text |Cite
|
Sign up to set email alerts
|

The migration of recirculating autologous and allogeneic lymphocytes through single lymph nodes

Abstract: Using cannulated single lymph nodes in sheep the migration of 51 Cr‐labeled autologous and allogeneic recirculating lymphocytes (RL) into efferent lymph was studied after i. v. infusion and infusioninto an afferent lymphatic. The majority of autologous and allogeneic RL appeared in efferent lymph 27–36 h after their infusion i. v. and 6–12 h after intralymphatic infusion. The recovery of i. v. infused allogeneic RL in efferent lymph was only 5–10% that of autologous RL. In contrast, there was no difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

1978
1978
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 20 publications
7
54
1
Order By: Relevance
“…By flow cytometry, 3 h after injection of labeled cells, 0.05 Ϯ 0.01% of the injected cells were recovered per 10 9 lymph node cells, but no labeled cells could be detected in the efferent lymph. Previous experiments have clearly demonstrated that the recirculation kinetics of labeled lymphocytes into afferent lymph parallels that seen in efferent lymph, and that virtually no labeled cells can be detected entering the lymph node via afferent lymph at this early time point (28,29). However, using flow cytometry, sufficient numbers of labeled cells could be clearly differentiated within the lymph node and phenotyped for conventional T and B cell subsets (Fig.…”
Section: Cd4 ϩ and ␥␦-Tcr ϩ T Cells Home To Sclns In Similar Numbersmentioning
confidence: 64%
“…By flow cytometry, 3 h after injection of labeled cells, 0.05 Ϯ 0.01% of the injected cells were recovered per 10 9 lymph node cells, but no labeled cells could be detected in the efferent lymph. Previous experiments have clearly demonstrated that the recirculation kinetics of labeled lymphocytes into afferent lymph parallels that seen in efferent lymph, and that virtually no labeled cells can be detected entering the lymph node via afferent lymph at this early time point (28,29). However, using flow cytometry, sufficient numbers of labeled cells could be clearly differentiated within the lymph node and phenotyped for conventional T and B cell subsets (Fig.…”
Section: Cd4 ϩ and ␥␦-Tcr ϩ T Cells Home To Sclns In Similar Numbersmentioning
confidence: 64%
“…Allogeneic T cells from postnatal lambs were used in our experiments because of the unavailability of inbred sheep. We felt justified in using allogeneic T cells because, unlike allogeneic T cells in adult sheep which do not recirculate to any extent, 14 the recovery of labelled allogeneic T cells in fetal lymph and lymph nodes is similar to autologous cells. This indicates that large numbers of allogeneic T cells are able to recirculate between blood and lymph in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the majority of cells in the afferent lymph vessels do not transit across into efferent lymph but remained in the lymph node 18 . In contrast, only a small fraction of the cells entering the efferent vessel are derived from the afferent lymphatic vessels or produced by multiplication within the node [19][20][21] . If this small fraction is required, the assumption that an LTI-SISO system is appropriate for studying peripheral lymphocyte migration becomes more reasonable.…”
Section: Introductionmentioning
confidence: 99%